2022
DOI: 10.3389/fnhum.2022.898633
|View full text |Cite
|
Sign up to set email alerts
|

Brain M-App’s Structure and Usability: A New Application for Cognitive Rehabilitation at Home

Abstract: Cognitive frailty is defined as a clinical condition characterized by both physical frailty and cognitive impairment, without reaching the criteria for dementia. The major goal of rehabilitation intervention is to assist patients in performing ordinary personal duties without the assistance of another person, or at the very least to remove the need for additional support, using adaptive approaches and facilities. In this regard, home-based rehabilitation allows patients to continue an intervention begun in a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…Our results were confirmed by recent studies on the usability of a tablet-based application designed for home-based cognitive rehabilitation which revealed a sufficient level of usability ( Pedroli et al, 2022 ).…”
Section: Discussionsupporting
confidence: 88%
“…Our results were confirmed by recent studies on the usability of a tablet-based application designed for home-based cognitive rehabilitation which revealed a sufficient level of usability ( Pedroli et al, 2022 ).…”
Section: Discussionsupporting
confidence: 88%
“…focused on a tablet‐based application designed for home‐based CR in CF individuals. The findings showed that it was both usable and well‐accepted among this population 84 . Nevertheless, the study had a relatively small sample size, and additional research, particularly feasibility and intervention studies, is required to provide more robust evidence and assess potential clinical advantages, including the reduction of CF 84 .…”
Section: Discussionmentioning
confidence: 93%
“…The findings showed that it was both usable and wellaccepted among this population. 84 Nevertheless, the study had a relatively small sample size, and additional research, particularly feasibility and intervention studies, is required to provide more robust evidence and assess potential clinical advantages, including the reduction of CF. 84 Long-term research is also needed to observe the impact of ICT use among CF individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have provided evidence of notable correlations between performance on VR tasks and traditional neuropsychological assessments that measure the same cognitive functions ( Matheis et al, 2007 ; Armstrong et al, 2013 ; Lalonde et al, 2013 ; Nolin et al, 2016 ; Pedroli et al, 2020 , 2022 ). This evidence confirmed that VR protocols effectively demonstrated construct validity.…”
Section: Introductionmentioning
confidence: 99%